A multi-color flow cytometric method for characterizing murine reticulated platelets using SYTO 13: technical report - Hamad, Muataz Ali; Krauel, Krystin; Schanze, Nancy; Zurek, Mark Maximilian; Olivier, Christoph; Kohl, Peter; Nührenberg, Thomas G.; Dürschmied, Daniel (Platelets, 2025)
Reticulated platelets (RP) are immature platelets with heightened RNA content. An increased level of RP in the circulation is associated with various pathological conditions. In this study, we employed a novel flow cytometry approach for RP detection in mice, utilizing the nucleic acid dye SYTO 13 in conjunction with a platelet-specific marker (anti-mouse CD42b-DyLight 649). The efficacy of SYTO 13 for RP identification was confirmed by higher circulating RP levels in platelet-depleted mice during the recovery phase (35% ± 13%) compared to untreated mice (11% ± 1%, n = 9, p < .0001). We further characterized murine RP by exploring the surface expression of the platelet activation marker P-selectin. While there was no preactivation at baseline, stimulation with a thrombin receptor agonist (PAR-4) resulted in a higher increase in the percentage of P-selectin-positive platelets in RP (93% ± 6%) compared to non-RP (77% ± 14%, n = 6, p = .0065). In addition, RP exhibited higher geometric mean fluorescence intensity levels than non-RP (1874 ± 1278 versus 859 ± 549, n = 6, p = .02). Our proof-of-principle study demonstrates the efficacy of SYTO 13 in combination with platelet (activation) markers for identifying RP in both resting and activated states. This method holds promise for simultaneously monitoring RP levels and platelet activation in murine models of human disease.